Development of Literacy Engagement in Chinese Students with Varying Language Proficiencies - Jiang, Apisak Sukying, Yilin; Sukying, Apisak (International journal of education and literacy studies, 2024)
The objective of this study is to develop literacy engagement in Chinese students with varying language proficiencies through teacher-written corrective feedback. Drawing on Bandura’s social cognitive theory and Boekaerts and Corno’s self-regulation theory, the research aims to understand how corrective feedback influences literacy engagement and language proficiency. The study employs a qualitative analysis of student responses and reflective journals with quantitative measures of language proficiency and engagement metrics. The research site includes Chinese university classrooms with both low-proficiency (LP) and high-proficiency (HP) students. Key informants are LP and HP students who receive teacher-written corrective feedback. Data analysis involves thematic coding of student responses and statistical analysis of language proficiency scores and engagement levels. Results show that LP students initially display passive engagement but improve with targeted feedback, while HP students demonstrate active engagement and advanced literacy skills. The study suggests tailored pedagogical strategies for LP students and challenges for HP students to enhance literacy engagement and language proficiency.